Doa Bapa Kami dalam Perspektif Kitab Suci - Rahmadi, Albertus Widya (Lux et Sal, 2024)
The “Our Father” prayer is one of the most recited prayers for all Christians. The Gospel of Matthew and Luke (Mat 6:9-13 and Luke 11:2-4) record this prayer as a prayer taught by Jesus himself to his disciples. This article aims at exploring the richness of this prayer by putting more light on its structure and meaning of some important expressions in the prayer. In general, there are six petitions in “Our Father” prayer, divided in two main sections. The first three petitions carry our thoughts toward Our Heavenly Father, for His own sake. The other three remind our necessities. By observing that, the article reveals that this prayer is very deep in meaning to help Christians grow in their devotional and spiritual life. Through its more devotional recitation, Christians would not only pray as a daily routine activity but also could actively grow in its awareness as disciple and in its confession of The Holy Trinity God.